Bewertung der Ökologie, Wirtschaftlichkeit und sozialen Effekte von ressourceneffizienzsteigernden Maßnahmen auf Quartiersebene – von der volkswirtschaftlichen zur akteursspezifischen Perspektive (NaMaRes): Schlussbericht des Forschungsvorhabens - Volk, Rebekka; Naber, Elias; Schultmann, Frank; Lützkendorf, Thomas; Mörmann, Kai; norra, stefan; Boehnke, Denise; Krehl, Alice; Schuhmann, Rainer; Ehbrecht, Anke; Beck, Thomas; Tomaschewski, Philipp; et al. (KIT Scientific Publishing, 2023)
The NaMaRes project developed tools and recommendations to support sustainable and resource-efficient urban planning at the neighborhood level. The considered resources include water, materials, land, and ecosystem services. The project's results enhance the information available on resources in existing neighborhoods and provide a foundation for stakeholders in political discussions and urban implementation planning. The project contributes to the implementation of the SDGs in cities.